2020
DOI: 10.1177/2329048x20946214
|View full text |Cite
|
Sign up to set email alerts
|

Protocol and Feasibility-Randomized Trial of Telehealth Delivery for a Multicomponent Upper Extremity Intervention in Infants With Asymmetric Cerebral Palsy

Abstract: Background: Past work showed that an in-person, therapist-guided, parent-implemented multicomponent intervention increased the motor functioning of the more affected upper extremity (UE) in infants with asymmetric cerebral palsy. The authors document treatment fidelity and provide initial testing of telehealth intervention delivery in a new subject sample. Methods: The authors adapted the intervention manual used in the previous trial for telehealth. Infants (6-24 months) were randomly assigned to intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…However, the review found no difference in unimanual capacity when CIMT was compared with high-dose or dose-matched occupational therapy or bimanual therapy 31. Consistent with this finding, 2 studies in this review found significant differences in unimanual capacity of the more affected hand when CIMT was compared with low-dose bimanual therapy 25,30. One study in this review found no difference in unimanual capacity of the more affected hand when CIMT was compared with dose-matched bimanual therapy 22.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…However, the review found no difference in unimanual capacity when CIMT was compared with high-dose or dose-matched occupational therapy or bimanual therapy 31. Consistent with this finding, 2 studies in this review found significant differences in unimanual capacity of the more affected hand when CIMT was compared with low-dose bimanual therapy 25,30. One study in this review found no difference in unimanual capacity of the more affected hand when CIMT was compared with dose-matched bimanual therapy 22.…”
Section: Discussionsupporting
confidence: 62%
“…All 4 studies with a total of 150 children with CP reported sufficient data on unimanual function of the more affected hand to be pooled for meta-analysis 22,23,25,30. The meta-analysis supported that children with unilateral CP who received CIMT (n = 79) scored an SMD of 0.59 (95% CI −0.18 to 1.37, P = .13; moderate effect) higher on unimanual function of the more affected hand compared with children with unilateral CP who received bimanual play or infant massage (n = 71).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The varying reported benefits of telemedicine along with the limitations of the clinical exam and the perceived cost of implementation have contributed to limited patient access to telemedicine in the past. However, the COVID-19 pandemic has necessitated the rapid conversion of many pediatric general and subspecialty clinics to telemedicine [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The research program piloted early interventions for infants with cerebral palsy (CP) through telehealth due to geographic restrictions stemming from a catchment area >150,000 km 2 . 5 Researchers adapted therapist assessments and physician neurological examinations for videoconferencing, even temporarily delivering examination kits, technology, or internet connectivity to homes. The clinical and research teams hypothesized that through collaboration with organizational partners in the hospital’s neonatal service line and experience in leveraging implementation science principles, they could develop an effective telehealth neurodevelopmental surveillance program for the youngest high-risk patients.…”
Section: Introductionmentioning
confidence: 99%